Gastrointestinal colonization and systemic dissemination by Candida albicans and Candida tropicalis in intact and immunocompromised mice. - de Repentigny, L (1992)
Gastrointestinal colonization and systemic dissemination by Candida albicans and Candida tropicalis were compared in intact and immunocompromised mice. Five-day-old CFW mice were inoculated by the oral-intragastric route with 1.0 x 10(7) CFU of two C. albicans and two C. tropicalis strains isolated from the blood of patients with acute leukemia and with C. albicans 4918 and its cerulenin-resistant mutant 4918-10. C. albicans and C. tropicalis spread to the lungs, liver, and kidneys within 30 min postinoculation, and organ CFU of the two species were comparable over the following 10 days. Close association of blastoconidia with the villous surface of the small intestine resulted in lysis of microvilli and then progressive invasion of villi. Blastoconidia within villi were surrounded by a conspicuous zone of clearing. Persistent colonization of the small and large intestines by C. albicans blood isolates and strains 4918 and 4918-10 was similar for 31 days after inoculation, but consistently exceeded that of C. tropicalis. In mice colonized with C. albicans, immunosuppression with cortisone acetate and cyclophosphamide on days 30 and 33 after inoculation increased stomach CFU 40- to 370-fold and intestinal CFU 30- to 80-fold. In contrast, persistent colonization by C. tropicalis was undetectable before immunosuppression and only became apparent after treatment. C. albicans disseminated more frequently and with higher organ CFU than C. tropicalis. Despite this fact, 20% of mice infected with C. tropicalis died, compared with 4% infected with C. albicans blood isolates. Indirect immunofluorescence revealed penetrative growth by Candida hyphae exclusively in the mucosa and submucosa of the stomach from immunosuppressed, persistently colonized mice. Taken together, the data indicate that C. tropicalis appears to be more virulent than C. albicans and that factors responsible for gastrointestinal colonization, systemic dissemination, and mortality in immunocompromised mice may not be identical.